Individual patterns and synchrony of heart rate variability in adolescent patients with borderline personality psychopathology and their mothers: a case-control study - Williams, Katharina; Fuchs, Anna; Kühn, Jana; Fleck, Leonie; Lerch, Stefan; Cavelti, Marialuisa; Koenig, Julian; Kaess, Michael (Borderline Personality Disorder and Emotion Dysregulation, 2025)
In adolescent Borderline Personality Disorder (BPD), interactions with caregivers often provoke dysregulation. Vagally-mediated heart rate variability (HRV), a physiological marker of regulatory capacities, shows alterations in BPD. Studies on individual and dyadic HRV in adolescents with BPD (BPD-A) and their mothers (BPD-M) are lacking. We examined 1) individual resting state -, reactivity- and recovery- HRV, 2) intrapersonal concordance of interactional quality with HRV, 3) mother-adolescent interpersonal HRV-synchrony and 4) the association of interpersonal HRV-synchrony with behavioral synchrony in a case-control design.